Brain-Based Learning as a Catalyst for Strengthening the Independent Dimension of Pancasila Student Profile in Islamic Religious Education - Nasriani Nasriani; Ni Wayan Savitry; Nina Ramadani (CV. Dharma Samakta Edukhatulistiwa, 2026)
The transformation of character education in Indonesia under the Merdeka Curriculum positions the Pancasila Student Profile as the foundational framework for national character development. However, at the elementary school level particularly in Islamic Religious Education and Character Education (IRE-CE) the internalization of the Independent Dimension remains hampered by low self-regulation and impulse control among students. This study aimed to implement Brain-Based Learning (BBL) with the John Elliott Classroom Action Research (CAR) model to strengthen the Independent Dimension of the Pancasila Student Profile among fourth-grade students at SDN 1 Dadakitan, Tolitoli Regency. Employing a mixed-methods participatory action research design across two cycles (four sessions) with 25 students, data were collected through structured observation using a nine-indicator Psychomotor Skills Rubric (0–4 scale) covering three latent variables: Compliance and Etiquette, Academic Engagement, and Resource Management. Data were analysed through descriptive quantitative methods and Partial Least Squares-Structural Equation Modeling (PLS-SEM) for causal validation. Results demonstrated a significant increase in classical mastery from a pre-cycle baseline of below 60% to 96% by the end of Cycle 2. PLS-SEM confirmed that Compliance and Etiquette significantly predicted Academic Engagement (β = 0.61, p < 0.001), which in turn significantly predicted Resource Management (β = 0.53, p < 0.001). The novelty of this study lies in its integration of PLS-SEM into classroom action research, elevating CAR methodology from anecdotal reporting to replicable statistical evidence. Findings offer a scientifically validated BBL protocol for IRE-CE teachers and contribute a new conceptual model of character formation rooted in educational neuroscience.